Implementation of Psychoeducation as a Strategy to Increase Career Adaptability in Vocational High Schools - Cici Ismuniar; Mega Septiani (Bisma The Journal of Counseling, 2023)
The online learning process makes students care less about learning, pay less attention to the teacher, and lack initiative in the practicum process. This has an impact on schools, teachers and students in carrying out the mentoring process in a different atmosphere from previous years. It can be said that implementing face-to-face learning for vocational school students is very necessary to hone students' skills. This research aims to analyze the application of psychoeducation as a strategy to increase career adaptability in vocational schools. This research is included in the type of experimental research, one group pre test-post test design. The population and sample in this study consisted of vocational school students. Data collection was carried out using a non-test method in the form of a Likert scale type questionnaire. Meanwhile, the data was analyzed using descriptive analysis methods. After several meetings and treatments, the results of this research show that there is an influence between career adaptability and the application of psychoeducation, there is additional information regarding career adaptability, and students understand career knowledge better after psychoeducation is carried out. It can be concluded that the application of educational psychology to improve career adaptability has an effect on increasing students' career adaptability, curiosity and self-confidence. The latest information in this research has implications for increasing the ability of vocational school students to adapt to career changes and prepare themselves to face the challenges of the world of work.